ChemInform Abstract: Aryl‐Free Radical‐Mediated Oxidative Arylation of Naphthoquinones Using o‐Iodoxybenzoic Acid and Phenylhydrazines and Its Application Toward the Synthesis of Benzocarbazoledione. Issue 31 (5th August 2014) - Patil, Pravin; Nimonkar, Abhay; Akamanchi, Krishnacharya G.
Abstract This method tolerates various functional groups.